Bishop Torhthelm's letter to Boniface. - Darby, Peter (Early Medieval Europe, 2025)
In c.738, St Boniface distributed a circular letter to a broad audience of ecclesiastics in England. One response to that letter survives, written by Torhthelm, bishop of the Middle Angles (737–64). The letter is written in an allusive style and borrows heavily from its main source, Pope Vitalian's letter to Oswiu, king of Northumbria. This essay offers a comprehensive study of Torhthelm's letter and provides new insights into the culture of letter‐writing in early medieval Mercia. The analysis also deepens our understanding of the relationship between that kingdom and the Continental mission during Æthelbald's reign.